Analisis Kemampuan Life Skills dan Literasi Lingkungan Berorientasi ESD Pada Siswa Sekolah Dasar - Rachmat Karno Utomo; Fenny Roshayanti; Nizaruddin (Postgraduate, University of Mataram, 2025)
This study is to identify the categories of life skills and environmental literacy abilities of fifth grade students of Mangkang Kulon 02 Elementary School, Semarang. This study is included in the type of development research, namely Research and Development (R&D) which refers to the ADDIE model. Data collection through google form, by providing a number of questions that include indicators of life skills abilities (WHO, 1997) and indicators of environmental literacy abilities (McBeth & Volk, 2009). The results of data analysis obtained the highest average percentage of students' life skills abilities in the personal skill indicator with a percentage of 43% in the sufficient category, while the lowest indicator in social skills was 28% in the weak category. In students' environmental literacy abilities, the highest percentage was 50% in the moderate category in the attitude indicator, while the lowest percentage was 32% in the low category in the behavior indicator. Based on the results of research and development, it is concluded that ESD-oriented learning devices are suitable for use in elementary school grade V science learning because they meet the criteria of validity, practicality and effectiveness. So that it can improve students' life skills and environmental literacy.